Mapping a Shared Ethos: Common Cultural Threads in Kannada Literature in English (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Kannada literature, with its rich trajectory from medieval Vachana poetry to modern experimental fiction, reflects a cultural ethos deeply rooted in Karnataka’s social, spiritual, and political life. When read in English—either through translation or critical commentary—this literature reveals common cultural threads that transcend individual writers and eras. This paper examines the shared ethos in the works of prominent Kannada literary figures such as Kuvempu, U. R. Ananthamurthy, Girish Karnad, Shivarama Karanth, and Vivek Shanbhag. Through themes of caste, folk traditions, spirituality, nature, gender, and modernity, their writings articulate a collective cultural imagination. Using textual analysis supported by critical literature, this study identifies how Kannada literature, when mediated through English, creates a cross-cultural discourse while retaining regional authenticity. The research demonstrates that despite stylistic differences, the writers collectively project Kannada culture as a dynamic negotiation of tradition and modernity, embodying what may be called a "shared ethos.".